2017
DOI: 10.1111/jfpp.13423
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasonic‐microwave synergistic extraction of polysaccharides from Morchella conica

Abstract: Ultrasonic‐microwave synergistic extraction (UMSE) was used to extract from Morchella conica polysaccharide (MCP). The effect of three independent variables (microwave power, ratio of water volume to raw material weight (W/M ratio), extraction time) on extraction yield was optimized using response surface methodology with a Box–Behnken design. The high R2 values (>.966) demonstrated the response and independent variables predicted by polynomial model were fitted. The optimal conditions for MCP extraction were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Performance of an UAE process is strongly linked to the surface characteristics of the plant material, but the contribution of individual processes, that is, surface erosion, peeling, and detexturization, depends on the structural rigidity of the subject material (Chemat et al, ). Xu et al () observed defined fractures caused by micro‐jetting on the solid surface of Morchella conica fruit cells and associated the rate of ultrasonic‐assisted extraction to the microstructural changes. Hence, the dilapidated structure of dried CCBs is beneficial for the performance of the UAE process.…”
Section: Resultsmentioning
confidence: 99%
“…Performance of an UAE process is strongly linked to the surface characteristics of the plant material, but the contribution of individual processes, that is, surface erosion, peeling, and detexturization, depends on the structural rigidity of the subject material (Chemat et al, ). Xu et al () observed defined fractures caused by micro‐jetting on the solid surface of Morchella conica fruit cells and associated the rate of ultrasonic‐assisted extraction to the microstructural changes. Hence, the dilapidated structure of dried CCBs is beneficial for the performance of the UAE process.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction of crude MCP was carried out according to the method described by Xu et al [33]. Briefly, the dried M. conica powder was defatted and decoloured in a Soxhlet apparatus, dried, and mixed with distilled water for extraction at the optimal extraction conditions (microwave power of 210.61 W, W/M ratio of 41.07:1, and extraction time of 126.98 s) in a UMSE(ultrasonic-microwave synergistic extraction) apparatus (XO-SM50, Nanjing Xianou Instrument Co. Ltd., Nanjing, Jiangsu, China).…”
Section: Methodsmentioning
confidence: 99%
“…Under appropriate conditions, the energy produced by ultrasound and microwave promotes cell rupture, enhance the interaction of intracellular material and solvent in less time, hence increase protein extraction rate. Nevertheless, when microwave power exceeded a certain value, the high microwave energy would disturb the interactions of molecular (Xu et al., 2018) and led to partial protein denaturation. Likewise, higher temperature or longer irradiation time for ultrasound and microwave extraction will destabilize the aqueous envelope of the proteins, destroy the hydrogen bond and structure of the protein, which could accelerate protein denaturation and precipitation, thus made the leaf protein solubility worse (Lv et al., 2019).…”
Section: Discussionmentioning
confidence: 99%